Efficacy and Safety Outcomes in Systematic Reviews of Interventions for Postoperative Pain in Children: Comparison Against the Recommended Core Outcome Set. Issue 11 (16th October 2017) - Boric, Krste; Dosenovic, Svjetlana; Jelicic Kadic, Antonia; Boric, Matija; Jeric, Milka; Puljak, Livia
Abstract: Objective: To investigate the range of efficacy and safety outcomes used in systematic reviews (SRs) of randomized controlled trials (RCTs) of interventions for postoperative pain in children and compare them with outcome domains recommended in the Pediatric Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials (PedIMMPACT). Methods: Five electronic databases were searched: MEDLINE, Cochrane Database of Systematic Reviews, DARE, CINAHL, and PsycINFO. Two review authors extracted outcome data independently. Efficacy and safety outcomes were extracted and categorized. The type and number of outcomes were analyzed and compared against the outcomes recommended by PedIMMPACT. The study protocol was registered in PROSPERO (CRD42015029654). Results: We included 48 systematic reviews with data from 816 trials. The median number of all outcomes was 4, while the median number of the PedIMMPACT core outcomes was three out of six. The most commonly reported outcome of the PedIMMPACT Core Outcome set (COS) was "symptoms and adverse events, " followed by pain intensity, which was reported in 75% of the included SRs. Just over half of the SRs that included a pain intensity outcome also indicated the specific pain assessment tool used in the methods section. Conclusions: Systematic reviews in the field of pediatric pain do not use the recommended COS. Nor do they consistently include pain as an outcome. This makes comparisons of efficacy and safety across interventions very difficult. Future studies should explore whether the authors are aware of the COS and whether the recommended COS is appropriate.